GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 89771148 species occurrences available in GBIF matching the query: { "HasCoordinate" : [ "is false" ] }. The dataset includes 89771148 records from 9900 constituent datasets: 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 186 records from Review of the Australian Cyllodini (Coleoptera: Nitidulidae: Nitidulinae), with descriptions of new taxa, and notes on the genus Macleayania (Nitidulini). 685 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 1 records from Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 14 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 49257 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 878 records from COA Bird Collection (Arctos). 54587 records from New Zealand Arthropod Collection (NZAC). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 1 records from Cetopirus complanatus (Cirripedia: Coronulidae) from the late Middle Pleistocene human settlement of Pinnacle Point 13 B (Mossel Bay, South Africa). 3 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 9949 records from University of Guam Insect Collection. 11274 records from National Botanic Garden Belgium - Myxomycetes. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 6 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 3 records from Morphological and molecular characterization of three Helicotylenchus species from Iran. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 2731 records from Museu de Ciències Naturals de Barcelona: BGJBB. 2 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 8 records from Lluciapomaresius nisae, a new species of Ephippigerini (Orthoptera: Tettigoniidae: Bradyporinae) from the northeast of the Iberian Peninsula. 12 records from Museo de Historia Natural, Colección de Vertebrados e Invertebrados - Colección Ictiológica. 2505 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 9 records from Redescription of four species of Cytaea Keyserling, 1882 (Araneae: Salticidae). 5 records from Additions to the leafhopper subgenus Pediopsoides (Pediopsoides) Matsumura, 1912 (Hemiptera: Cicadellidae: Macropsinae) from Southern China. 6 records from An updated and detailed taxonomical account of the large Branchiopoda (Crustacea: Branchiopoda: Anostraca, Notostraca, Spinicaudata) from the Yale North India Expedition deposited in the Yale Peabody Natural History Museum. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 11 records from orthopteracollections-nhmj-ioj. 45 records from Bird specimens of Saitama Museum of Natural History. 114 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 2 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 3 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 25 records from (Fig. 9B) Compiled data of profile Pré-Guittard, SE France. 24370 records from Muséum d'Avignon. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 3 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 3895 records from Plant specimens of Tama City Cultural Foundation. 4 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 4 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 7 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 19 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 8 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 4 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 8 records from NZCS Raleighvallen-Voltzberg Monitoring 1997/1998/2000/2009. 3 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1 records from Nothrus pulverulentus. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 7 records from On the taxonomy and morphology of Leuthneria ruficincta (Lepidoptera: Sesiidae). 2 records from Condamine Alliance. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 44 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 2 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 58 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 33 records from Tardigrad collection of the National Museum of Nature and Science. 7600 records from Observational database of Icelandic plants. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 7 records from Speolabeo, a new genus name for the cave fish Bangana musaei (Teleostei: Cyprinidae). 6 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 4550 records from Herbier Louis-Marie (QFA) - Collection de lichens. 255 records from Actualización de la Colección de Microorganismos de importancia acuática. 69396 records from ECatSym: Electronic World Catalog of Symphyta. 16 records from A new genus and species of natricine snake from northeast India. 4 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 1179 records from Brown University. 607514 records from Plant. 982 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 166 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 1 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 5576 records from Colecção Entomológica IIA. 1266 records from Actinomycetes Collection in BCRC. 4 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 392 records from MZFC/Coleccion de Aves. 4567 records from Herbarium WRSL, Main Collection. 248 records from Orca observations from the shores of Macquarie Island. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 4789 records from Colección Mastozoológica del IADIZA - CCT CONICET Mendoza: IADIZA-CMI. 428 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 6165 records from DMNS Egg Collection (Arctos). 7 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 1720 records from Lepidopterous specimens of Yamagata Prefectural Museum. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 2 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 214 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1277 records from Museu Paraense Emílio Goeldi - Chelonia Collection. 213 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 4 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 26 records from An updated checklist of aquatic plants of Myanmar and Thailand. 2593 records from Colección de Poales del Museo Botánico CORD - IMBIV. 436 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 750 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 9 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 14529 records from Collection Coleoptera SMF. 80 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 17 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 128 records from List of invasive or harmful alien species in Wallis and Futuna Territory. 2 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 76 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Mollusca (ZUFMS-MOL). 24 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 2 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 12161 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 2 records from KTU Pteridophyta. 12 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 4 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 1 records from A new species of Ferneiella from the Eocene French amber (Diptera: Scatopsidae). 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 2 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 65272 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 29 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 1591 records from CNIN/Abejas de México/Apoidea. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 7 records from Freshwater fish records via iRecord. 264 records from Flora útil del Municipio de la Huerta, Jalisco. 109063 records from Slovenian Fungal Database - Boletus informaticus. 8 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 9 records from The Diptera Site. 228 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 12 records from Endogean and cavernicolous Coleoptera of the Balkans. XVII. A new species of the genus Speluncarius Reitter, 1886 (Coleoptera, Carabidae, Harpalinae, Pterostichini) from Croatia. 2 records from Two small species of Cremohipparion (Equidae, Mammalia) from Samos, Greece. 3 records from Two new brackish-water species of Macrostomum (Platyhelminthes, Macrostomida) from mangrove wetland in southern China. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 4 records from A new genus of Silvaninae (Coleoptera: Silvanidae) with two new species from the Malay Peninsula. 74 records from Review of the horse flies of the genus Atylotus Osten Sacken, 1876 (Diptera: Tabanidae) from Egypt, with description of a new species. 10354 records from Herpetological collection of National Museum of Nature and Science. 6 records from Moema apurinan sp. n. and Aphyolebias boticarioi sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new annual killifishes from the Rio Purus basin, Brazilian Amazon.. 1 records from Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia. 114988 records from Naturalis Biodiversity Center (NL) - Crustacea. 33 records from The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae). 329 records from Amphibian and Reptilian (KIEE-AR). 12147 records from Danish Ants (Formicidae). 4 records from Brown algae specimens of Komatsu City Museum. 23928 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 49 records from Ascomycetes of Russian Fennoscandia. 500 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Remarkable new fossil species of Schistostoma Becker (Diptera: Dolichopodidae Microphorinae) from mid-Cretaceous Burmese amber. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 241 records from Fishes of the Cusiana River (Meta River basin, Colombia). 314 records from Colecção Entomológica do Departamento de Sanidade Vegetal - Ministério da Agricultura e Segurança Alimentar. 1659 records from The Broward College Insect Collection. 1349 records from Ibaraki Nature Museum, Mammals collection. 1225 records from Seawater carbonate chemistry and Gadus morhua length, weight and sperm biological processes, 2010. 24269 records from Berea College, Ralph L. Thompson Herbarium. 15 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 58 records from Cephalomalthinus simplicicornis (Wittmer, 1993) rev. stat. et comb. n.: a resurrected soldier beetle (Coleoptera, Cantharidae) from Taiwan based on morphological and molecular data. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 1 records from Description of a new species of Hyalinocerus (Hemiptera: Cicadellidae) from southwestern China, with an update on the generic diagnosis. 2 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 19 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 2 records from The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island. 14 records from Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 28 records from Plant - Plant Virus (KIDR-PL). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 8446 records from MEXU/Leguminosae. 118454 records from KUBI Paleobotany Collection. 117269 records from Coleção Entomológica do Museu Nacional / UFRJ. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 3 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 85874 records from Canadian Museum of Nature Herbarium. 99 records from A taxonomic monograph of the assassin bug genus Zelus Fabricius (Hemiptera: Reduviidae): 71 species based on 10,000 specimens. 519 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 264 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 2 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 50873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 18 records from CNIN/Tipos Lepidoptera. 5 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 13 records from New Species and Records of Costa Rican Featherwing Beetles (Coleoptera: Ptiliidae). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 326 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 16614 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 4 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 1 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 7 records from Sertania gen. nov., a new genus of butterflies (Lepidoptera: Riodinidae) from the South American dry diagonal. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 2 records from New species and records of Scaphobaeocera CSIKI from New Guinea (Coleoptera: Staphylinidae: Scaphidiinae). 6 records from Re-description of two spiny clam shrimps (Crustacea: Branchiopoda: Spinicaudata) of the Indian subcontinent from Daday de Dees's collection at MNHN with new insights on the validity of Eulimnadia compressa (Baird, 1860) and Eulimnadia chaperi (Simon, 1886). 95 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 282 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 122060 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 19525 records from Bolus Herbarium: Bryophyte and Ericaceae (1641-2016). 134 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord. 3918 records from Collembola Collection. 6 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 120 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 5 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 10 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 192 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 31 records from Nothogreniera new genus, for two species of Australian " Paracnephia " (Diptera: Simuliidae). 51265 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 582 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 15 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 8454 records from Colección de Hongos del Herbario de la Universidad de La Laguna: TFC Mic. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5406 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 30 records from A checklist of the millipedes (Diplopoda) of Myanmar, with an updated list of Leonardo Fea’s collecting localities. 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 1 records from Hymenoptera: Eucoilinae (Cynipoidea). 1 records from A new species of the genus Sazonia O. Gorbunov & Arita, 2001 from Vietnam (Lepidoptera: Sesiidae). 2814 records from 16S rRNA metagenomic investigation of arsenotrophic bacteriome of ground water and soil from arsenic-prone area of Bangladesh. 4 records from Two new species of the water scavenger beetle genus Hemiosus Sharp (Coleoptera: Hydrophilidae) from Colombian Andes. 1 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 52 records from M. Gollop Collection. 53204 records from Naturalis Biodiversity Center (NL) - Diptera. 3 records from Trachyuropodid mites (Acari: Uropodina) from South-East Asia: catalog, new key and description of two new species. 5 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 1 records from Berlese's Primitive Oribatid Mites. 42 records from Arachnologie ZMK. 11 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 306 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 9 records from NatureShare. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 1 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 3553 records from Mycology herbarium, Tromsø Museum. 13 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 2 records from Description of the immature and adult stages of the jujube tube spittlebug Machaerota planitiae Distant (Hemiptera: Cercopoidea: Machaerotidae) in Bangladesh. 24 records from A review of the stink bug genus Plautia Stål from Japan (Hemiptera, Heteroptera, Pentatomidae). 1010 records from University of Minnesota Insect Collection. 2860 records from ARABEL - Arachnologia Belgica. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 87 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 98 records from UCM Vertebrate Observations Collection (Arctos). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 19 records from Seabird Observations, Storm Bay, Tasmania, Australia, 1991-1994. 1839 records from MLZ Bird Collection (Arctos). 21 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 25 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 13 records from Taxonomy of calcareous sponges (Porifera, Calcarea) sampled on artificial substrates of a recreational marina in the Tropical Northeastern Brazilian coast. 2 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 5 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). I. Gracilipalpe, morchella and nigrum groups. 5 records from UWYMV Herpetology Collection (Arctos). 60623 records from Herbarium Senckenbergianum (FR) - Fungi. 6 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 2 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2007 records from Plant specimens of Bihoro Museum. 1867 records from Mushroom Collection in BCRC. 35 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 198819 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.]. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 13 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 61 records from Espèces végétales inventoriées dans les formations et strates de la forêt communautaire de Koussountou au Togo en 2017.. 31394 records from NCSM Vertebrate Paleontology Collection. 5 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 1 records from QLD DERM Coastal Bird Atlas (Trial). 37725 records from SPSF - Herbário Dom Bento José Pickel. 27 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 8 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 23 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 176 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 32 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 6 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 2818875 records from Natural History Museum (London) Collection Specimens. 2 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 49 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 1 records from Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2532 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 758 records from Colección Ictiológica del Instituto Alexander von Humboldt. 33 records from The Gomphocerinae Tarbinsky, 1932 (Orthoptera: Acrididae) fauna of the Turkish Thrace. 7 records from Two new species of Quichuana Knab (Diptera: Syrphidae) from the paramo ecosystems in Colombia. 62771 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 65 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 55 records from Collection botanique Jaubert et Saul (BOUM). 2 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 5 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 1 records from Pelops tardus. 20 records from NZCS Sipaliwini Savanna Expeditions 1997/2014. 2 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 10875 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 3 records from Two new species of Polana (Hemiptera: Cicadellidae: Iassinae: Gyponini) and redescription of Polana (Striapona) desela. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 1242 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 4772 records from National Plant Monitoring Scheme - England, Scotland, Wales. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 2 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 45 records from Morphological and genetic evolution in eastern populations of the Macrhybopsis aestivalis complex (Cypriniformes: Cyprinidae), with the descriptions of four new species. 9 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 331 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 2 records from New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico). 1952 records from ISM Ichthyology Collection. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 10 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 3 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 4 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 27 records from A new species of crayfish in the genus Orconectes (Decapoda: Cambaridae) from the Tennessee River Drainage with comments on and key to members of the O. juvenilis Species Complex. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 4 records from Tanycarpa broadi sp. nov., a new Neotropical species of the genus Tanycarpa Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae), with a key to the New World taxa. 4713 records from The Himalayan Uplands Plant database (HUP Version 1). 34115 records from DMNH Birds. 142 records from Database on reference specimens for medicinal plants of the Euphorbiaceae family, conserved at the CNARP herbarium. 14333 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from Zetes flavipes. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 3 records from Amended diagnosis and redescription of Pristimantis marmoratus (Boulenger, 1900) (Amphibia: Craugastoridae), with a description of its advertisement call and notes on its breeding ecology and phylogenetic relationships. 1085 records from Global Ocean Sampling Expedition. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 6 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1575 records from Hermatypic Corals of Western Australia. 269 records from Collections ichtyologiques et herpétologiques (BOUM). 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 1520 records from Rutgers University, Chrysler Herbarium - Lichen Collection. 12 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 89 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 1 records from La collection Gilles Becquet (BOUM). 252 records from Norwegian Lepidoptera working group. 2 records from A new cicada species of Psalmocharias Kirkaldy feeding on an Ephedra plant from China (Hemiptera: Cicadidae). 8 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 20 records from Northern Biodiversity Program Coleoptera (2010-2011). 34 records from Validity of Psammoperca datnioides Richardson 1848 and redescriptions of P. waigiensis Cuvier in Cuvier & Valenciennes 1828 and Hypopterus macropterus (Günther 1859) in the family Latidae (Perciformes) from the Indo-West Pacific. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 1 records from New records of Synallactes virgulasolida Massin & Hendrickx, 2010 (Echinodermata: Holothuroidea) from the eastern Pacific. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 2 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 113 records from National Museum of Marine Biology and Aquarium. 45 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 6764 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal). 270 records from bmhs_weatherheadshell_collection. 6 records from Immature stages of the genus Oxythyrea (Coleoptera: Scarabaeidae: Cetoniinae) with a key to third instar larvae, and notes on the biology of the genus. 13 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 35 records from Anthomyiidae, Fanniidae and Muscidae (Diptera) from the Juan Fernández Archipelago (Chile): 60 years after Willi Hennig’s contributions. 323 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 105 records from Living Cirripedia. 2 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Notes on the biology and distribution of the tribe Agallissini in North America (Coleoptera: Cerambycidae: Cerambycinae). 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 6 records from A new four-pored Amphisbaena (Squamata: Amphisbaenidae) from northeastern Brazil. 14426 records from CCBER Herpetology Collection. 13 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 35 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 3 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 1 records from New species of the anthiadin genus Sacura (Perciformes: Serranidae) from the Andaman Sea. 6 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 84 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 18 records from New genus to science of Meconematinae (Orthoptera: Tettigoniidae) from China with description of two new species and proposal of one new combination. 77 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 7423 records from University of California Santa Barbara Invertebrate Zoology Collection. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 3 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 1 records from Nothrus biverrucatus. 1 records from A review of the taxonomy and osteology of the Rhombophryne serratopalpebrosa species group (Anura: Microhylidae) from Madagascar, with comments on the value of volume rendering of micro-CT data to taxonomists. 129 records from Herpetofauna del Estado de Veracruz. 1234 records from Entomology Collection at the Natural History Museum of Utah. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 930 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 1 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 33 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 24 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia.. 88 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 4247 records from Australian National Insect Collection. 3175 records from Herbarium specimens of Limoges university (LIMO). 8 records from A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka. 1097 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 41162 records from Fish specimens of Kagoshima University Museum. 75 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4 records from Rivaling the World’s Smallest Reptiles: Discovery of Miniaturized and Microendemic New Species of Leaf Chameleons (Brookesia) from Northern Madagascar. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 3691 records from UTEP Invertebrates (Arctos). 353 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 998 records from Korean Ethnobotany Database. 1 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 2 records from Marthamea bayae, a new species of stonefly from Algeria (Plecoptera: Perlidae). 28 records from The catshark genus Scyliorhinus (Chondrichthyes: Carcharhiniformes: Scyliorhinidae): taxonomy, morphology and distribution. 2 records from Schizopyga alinae, a genus of pimpline parasitoid wasps (Hymenoptera: Ichneumonidae: Pimplinae) new to the Afrotropical region. 4 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 2 records from A new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam with description of two new species. 765 records from The Fungal Collection at the Botanische Staatssammlung München. 19 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 47 records from Calvariopsis gen. nov., a new genus of Neotropical Scirtidae (Coleoptera: Scirtoidea). 998554 records from Phanerogamic Botanical Collections (S). 196 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 4996 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 31 records from A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae). 14731 records from Herbarium specimens of Hokkaido University Museum. 2 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 174 records from Lichen specimens of Okinawa Prefectural Museum & Art Museum. 19 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 2 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 8 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 3 records from New species of Lonchaeidae (Diptera) from Switzerland and Serbia with arevised checklist of the Swiss fauna. 1 records from Papilio Sticheli nov. spec. aut subsp.. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 73 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ben Hell. 270 records from Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini). 17 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 1 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 342 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Callogorgia lucaya sp. nov., a new species of deep-sea Primnoidae (Anthozoa: Octocorallia) from the western Atlantic. 871 records from FLORA REGIONAL Y OTROS PAÍSES. MMHNSR 2018. 32438 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 17 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 8608 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 4 records from Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 61 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 16 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 71 records from A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia. 104 records from Mammalogie ZMK. 10 records from Checklist of the Free-Living Marine Nematodes of the Iberian Peninsula (north east Atlantic). 80 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 415 records from Flora d'Andorra. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 15 records from Conringia orientalis. 4 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 4 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 90 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 44 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 9 records from Discovery of the genus Pseudepione Inoue, 1943 in Taiwan, with description of a new species (Lepidoptera: Geometridae: Ennominae). 1 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 6356 records from Green Edge microcosms Raw sequence reads. 5 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1212 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 1 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 5 records from Two new and potentially highly threatened Megophrys Horned frogs (Amphibia: Megophryidae) from Indochina’s highest mountains. 4 records from Two remakable new species of Notocera Amyot and Serville, 1843 (Hemiptera, Membracidae, Hypsoprorini) from the Brazilian Caatinga. 111 records from University of Guelph Insect Collection (DEBU). 14 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 4 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 5 records from Solitary bees collected in a large-scale field experiment in power line clearings, southeast Norway. 7 records from Redescription and new records of a poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, and description of a new species of Pseudophilyra from Japan (Crustacea: Decapoda: Brachyura). 1361 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 28 records from Korean Plant Virus Database. 15 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 30 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 29 records from Herbarium Senckenbergianum (FR) - Protista. 836 records from Colección de Zoología Invertebrados - Carcinología. 563 records from Antarctic Marine Protists species checklist. 1 records from New earthworm records (Clitellata: Lumbricidae) from Bulgaria since 2012. 3 records from Zoology in the Middle East. 375 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 3947 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 7 records from Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil. 2 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 990 records from Records of the Australian National Botanic Gardens Seedbank. 3817 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 4 records from Lista florística de la Costa Grande del estado de Guerrero. 1 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 15 records from A new genus and four new species of subfamily Cyclocypridinae (Crustacea, Ostracoda) from Thailand. 35 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 2 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 6 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 9 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 2858 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 11 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 30 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 13 records from Redescription of the Indo-West Pacific scorpionfish Scorpaena neglecta Temminck & Schlegel, 1843, a senior synonym of four nominal species (Teleostei: Scorpaenidae). 1 records from Nothrus pigerrimus. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 4 records from Herpetology Collection. 230 records from Pilularia Globulifera distribution map in Denmark. 5896 records from UF FLMNH Ichthyology. 40 records from Seawater carbonate chemistry and boron incorporation of planktic foraminifer Orbulina universa during experiments, 2011. 194 records from (Fig. 4) Nannofossil abundance of Cretaceous profile L´Arboudeysse, SE France. 10 records from Two new species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) from Brazilian caves. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 132 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 18 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 8 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 17367 records from K-State Museum of Entomological and Prairie Arthropod Research. 1 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 2 records from On the taxonomic status of amphidromous shrimp Paratya borealis Volk, 1938 (Crustacea: Decapoda: Atyidae) from the south of the Russian Far East. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 1180 records from Studies on the Australian Muscidae (Diptera). VIII. The genus Lispe Latreille, 1797. 2 records from Youngest representative of the extinct genus Microphorites in the Eocene amber of France (Diptera: Dolichopodidae: Microphorinae). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 24523 records from European Moth Nights. 5 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) from northwestern Vietnam. 18 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 64 records from The congrid eel genus Ariosoma in Taiwan (Anguilliformes: Congridae), with description of a new species. 159 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 688 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 8 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 27596 records from Field Museum of Natural History (Botany) Fungi Collection. 19 records from The family Bombyliidae in the Kingdom of Saudi Arabia (Diptera: Brachycera: Asiloidea). 1 records from Nothrus echinatus. 11794 records from SJRP - Herbário de São José do Rio Preto. 1 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 66 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 60 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 5 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 943 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 1 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 164 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 58 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 27 records from Empria and Monsoma in Japan. 21 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 394 records from Reptilia ZMK. 56 records from DNA barcodes from century-old type specimens using next-generation sequencing. 1383 records from Plant observations from Białowieża National Park. 26031 records from Ibaraki Nature Museum, Vascular Plants collection. 2 records from A redescription of Moina australiensis Sars, 1896 (Cladocera: Moinidae) with short notes on Australian moinids. 3 records from Hylaperdina squamosa, a new species of Neotropical Lycoperdininae (Coleoptera, Endomychidae) from Brazil. 38149 records from University of Ghana - Ghana Herbarium. 45 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 24408 records from Birds (JNHM-BI). 4887 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 37 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 37 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 226 records from Catálogo de los equinodermos recientes de México (Fase II). 1 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 17 records from ScoliorhAPis stEPAnovi - new species of sea cucumber from the North-West Pacific (Holothuroidea: Synaptida: Chiridotidae: Taeniogyrinae) and some remarks on the genus ScoliorhAPis. 689 records from Inventario de Hymenóptera; parasítica en México. 160201 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 4 records from Amazoniaseius imparisetosus n. sp., n. g.: an unusual new phytoseiid mite (Acari: Phytoseiidae) from the Amazon forest. 1 records from Two species of the conifera - subgroup of Triconia (Copepoda, Oncaeidae) from the northeastern equatorial Pacific, with a description of the unknown male of T. hirsuta. 45 records from Onuphi s and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918. 1 records from A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) on fig trees in Iran. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 22516 records from MfN - Fossil Fish Collection. 1 records from Morphotaxonomic revision of species-groups of Simulium (Simulium) (Diptera: Simuliidae) in the Oriental Region. 4 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 717 records from Insect Collection of Saitama Museum of Natural History. 35 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 2403 records from DSMZ Collection of Filamentous Fungi and Yeasts. 10 records from Two new species of lotic breeding salamanders (Amphibia, Caudata, Hynobiidae) from western Japan. 11 records from List of leaf beetles (Coleoptera: Chrysomelidae) from Lagodekhi reserve with new records for Transcaucasia and Georgia. 1393 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 98 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 3298 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 8 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 2 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 110 records from IBF Monitoring of Plant Galls. 239416 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 6 records from Discovery of two new Andean species of Scolomus (Townes & Townes), with a key to all known species (Hymenoptera: Ichneumonidae: Metopiinae). 132 records from Birds Specimens of Akita Prefectural Museum. 2 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 26800 records from MSUM Ichthyology and Herpetology Collections. 8 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 16809 records from Genebank, National Institute of Agrobiological Sciences. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 7 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 276 records from Eurobodalla Regional Botanic Gardens. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 1 records from Great Eastern Ranges - Slopes to Summit. 47 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 2911 records from Tiroler Landesmuseum Ferdinandeum. 4 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 78 records from Mammals (GNHM-MM). 1 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 60 records from Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region. 158 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 2 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 3 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 3353 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 1 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 2 records from Database on reference specimens for medicinal plants of the Araceae family, conserved at the CNARP herbarium. 48 records from A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia. 46 records from The genera and species of the Brueelia - complex (Phthiraptera: Philopteridae) described by Mey (2017). 1442 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 2792 records from Fundación Miguel Lillo - Colección Invertebrados. 54 records from A catalog of Acroceridae (Diptera) from Chile. 3824 records from Collection Messelpaläobotanik SMB. 23836 records from Birds (KIDR-BI). 1 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 200 records from Bird specimens of Kushiro City Museum. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 696 records from CNMT - Herbário Centro Norte Mato Grossense. 1 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 528 records from Collection Hydrozoa - ZSM München. 40 records from Two new cichild species Neolamprologus (Teleostei: Cichlidae) from Lake Tanganyika, East Africa.. 19 records from The eel genus Macrocephenchelys (Anguilliformes: Congridae) in Taiwan, with description of a new species. 1 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Taiwan, with keys to all 13 species of the Simulium varicorne species-group. 24795 records from Université d'Aix-Marseille. 31 records from Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America. 4 records from Hyolithen - SMF. 1 records from Murcia trimaculata. 3 records from MfN - Micropaleontology. 19 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 6 records from Birds and plant species near Petushki town (Vladimir region). 34 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres presentes en Papigochic y su zona de influencia.. 386 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 6 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 3 records from An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea). 55 records from Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae). 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 18184 records from Herpetology. 1544 records from Porifera MZS. 85 records from UWYMV Bird Collection (Arctos). 24 records from A new species of Bedotia (Teleostei: Atherinomorpha: Bedotiidae) from the Rianila drainage of Eastern Madagascar, with redescriptions of Bedotia madagascariensis and Bedotia geayi.. 72 records from OSAC North American Cossoidea -beta version. 13458 records from inatura - Erlebnis Naturschau Dornbirn. 3 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 12 records from A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 6717 records from LSUMZ Mammal Tissues. 65 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 126493 records from PlutoF platform observations. 4 records from A new species of Acanthosaura Gray 1831 (Reptilia: Agamidae) from central Vietnam. 1 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 1 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 221 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1448 records from Herbario de Universidad de Murcia: MUB. 74 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 107580 records from Database of invertebrates collected in Mongolia. 37 records from Checklist of decapods (Crustacea) from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: I. Infraorder Caridea: families Hippolytidae, Lysmatidae, Ogyrididae, Processidae and Thoridae. 24 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 32916 records from Insect specimen database of Atsugi City Museum. 71 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 2989 records from Sponge collection of National Museum of Nature and Science. 356 records from Morphologische Daten von Puffinus creatopus. 2 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 132615 records from South Australian Museum Australia provider for OZCAM. 6 records from New anaxyelids (Hymenoptera: Anaxyelidae) from the Cretaceous of Asia. 23 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 872 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 586 records from Colección de Polypodiales, Proteales, Psilotales y Ranunculales del Museo Botánico CORD - IMBIV. 148 records from Herbarium BSG Hepaticopsida. 10 records from Arachnid specimens of Okinawa Prefectural Museum & Art Museum. 10 records from Descriptions of eight new species of the genus Parancistrocerus Bequaert (Hymenoptera: Vespidae: Eumeninae), with a key to the Oriental species. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 13005 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 3 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 35 records from Invasive Alien plant species of Malawi. 16 records from Colaphellus palaestinus Achard, a new leaf-beetle for Europe (Coleoptera, Chrysomelidae, Chrysomelinae). 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Podicipedidae. 299 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 20 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 37 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 28 records from Checklist of the freshwater snails (Mollusca: Gastropoda) of Mongolia. 2 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 2024 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 6491 records from Les Rubiaceae, Orchidaceae, Moraceae, Sapindaceae, Malvaceae, Melastomataceae, Verbenaceae, Loganiaceae, Sapotaceae, Scrophulariaceae, Sterculiaceae, Liliaceae, Meliaceae, Ochnaceae, Tiliaceae, Rosaceae, Solanaceae, Violaceae, Zingiberaceae, Myrtaceae, Rutaceae, Loranthaceae et quelques 71 autres familles de plantes de l'Herbier du Centre National de Floristique en Côte d'Ivoire.. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 1 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 13 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 5 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 760 records from Arthropoda specimens of Toyama Science Museum. 77 records from Incorporation of Mg and Sr in calcite of cultured benthic foraminifera (Heterostegina depressa and Ammonia tepida) and seawater carbonate chemistry, 2010. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 9 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 1 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 48 records from Fiocruz/CFP - Coleção de Fungos Patogênicos. 4 records from A name for the nurse-frog (Allobates, Aromobatidae) of Floresta Nacional de Carajás, Eastern Brazilian Amazonia. 3 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 32 records from Systematic revision of Central American Calligrapha Chevrolat of the subgenus Erythrographa subgen. nov. (Coleoptera: Chrysomelidae, Chrysomelinae). 2 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 6 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 1 records from On two new synonyms of the orb-weaving spider Orsinome vethi (Hasselt, 1882) (Araneae, Tetragnathidae). 3 records from New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 28 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 3 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 77396 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 795 records from Histoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 22 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 6 records from Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae). 3695 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 11 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 34 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 32 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 10213 records from Mammals Specimens. 1 records from Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 1 records from A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China. 7224 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 6 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 16 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 36 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 17 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 24 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 1 records from Murcia acaroides. 214 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 94 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 20 records from NZCS Brownsberg Nature Park Monitoring. 852 records from ANTARCTIC PLANT DATABASE. 1 records from Craspedorrhynchus linardii, a new species of chewing louse (Phthiraptera: Ischnocera: Philopteridae) from the Gray-headed Kite (Aves: Falconiformes: Accipitridae). 5 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 112 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 5 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 5 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 2 records from A contribution to the systematics of Salea anamallayana (Beddome, 1878) and S. horsfieldii Gray, 1845 (Squamata: Agamidae: Draconinae). 68 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 9 records from First record and new species of the Oriental leafhopper genus Trifida Thapa & Sohi (Hemiptera: Cicadellidae: Typhlocybinae) from China. 34 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 73 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 12 records from Towards the taxonomy of Corynoneura Winnertz (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East and Eastern Siberia. 5255 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 291 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 1 records from Echinoderms from the Seaflower Biosphere Reserve. 1 records from A new species of hydrothermal vent stalked barnacle Vulcanolepas (Scalpelliforms: Eolepadidae) from the North Fiji Basin, Southwestern Pacific Ocean. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 1 records from Celaeno obsoleta. 191251 records from Allan Herbarium (CHR). 202947 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from Four palaeonemerteans (Nemertea: Anopla) from a tidal flat in middle Honshu, Japan. 3 records from Miltochrista wangmini, a new species from China (Lepidoptera, Erebidae, Arctiinae). 3 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 350 records from Fungal Collection of Natural History Museum and Institute, Chiba. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 27 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 3 records from MVZ Herp Observations (Arctos). 2 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 177 records from Cercle des mycologues de Montréal Fungarium (CMMF). 3 records from Aquatic microdrile Oligochaeta (Annelida, Clitellata): New nominal taxa and combinations since 1984. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 3 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 3994 records from Uncultured eukaryotes Targeted Locus (Loci). 1532 records from Restauración y conservación de Isla Guadalupe. 3 records from Systematic census of the private plantations of the firewood of the Benin .. 38412 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 382 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 81157 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 16 records from Mascarapion, a new genus of the Apioninae (Coleoptera, Curculionoidea) from the Mascarene Islands. 32 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 20897 records from Marie-Victorin Herbarium (MT) - Bryophytes. 12 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 8 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 53 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 1 records from First record of the cicadas genus Orientopsaltria Kato, 1944 (Hemiptera: Cicadidae) from Vietnam, with description of one new species. 17 records from Three new species of genus Mecopoda Serville, 1831 from China (Orthoptera: Tettigoniidae: Mecopodinae). 11 records from Nematomorpha from Hong Kong and description of a new species from Malaysia. 1 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 80 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 16 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 96726 records from Buffalo Society of Natural Sciences Clinton Herbarium. 1 records from Schistobrachia kabata sp. nov. (Siphonostomatoida: Lernaeopodidae) from rajiform hosts off South Africa. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 1537 records from Utah State University, Intermountain Herbarium. 44 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 16 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 19 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 223486 records from Phytochorologie des départements français. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 184394 records from CAS Entomology (ENT). 12985 records from CNIN/Thysanoptera. 33136 records from Naturalis Biodiversity Center (NL) - Pisces. 27491 records from Carnet B Lorraine. 96 records from Molluscan fauna of Gueishan Island of Taiwan. 5 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 22 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 84 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 17 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 760 records from Insect Ichneumon fly (KIDR-IN). 41 records from A taxonomic revision of the genus Sirthenea (Hemiptera: Heteroptera: Reduviidae) of the Old World. 1 records from Enlarging the monotypic Monocarpieae (Annonaceae, Malmeoideae): recognition of a second genus from Vietnam informed by morphology and molecular phylogenetics. 3 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 11028 records from Collection Trichoptera - SMF. 1701 records from MfN Fish Collection, Zoology. 33778 records from Insect specimens of Tochigi Prefectural Museum. 95 records from Lichenized fungi of Vietnam (PHH Herbarium, Cryptogam collection). 5 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 103 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 5 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 1 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 557 records from Arizona State University Hasbrouck Insect Collection. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 13570 records from Royal Botanical Gardens Herbarium. 430 records from Collection Strepsiptera SMF. 25592 records from Herbarium Amazonense. 23499 records from Vascular plant herbarium TRH, NTNU University Museum. 2 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1121 records from USAC Mammals Collection. 19 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 47 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 3 records from Description of the mature larva of Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941 (Coleoptera: Elmidae). 1 records from The tenth member of stout newt (Amphibia: Salamandridae: Pachytriton): Description of a new species from Guangdong, southern China. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Donacobiidae. 2603 records from Museu Paraense Emílio Goeldi - Paleoinvertebrate Collection. 4513 records from SMNS Herpetologie. 5 records from Redescription of a little-known spider species, Mesiotelus lubricus (Simon, 1880) (Aranei: Liocranidae) from China. 60 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 2068 records from Colección Zoológica de la Universidad del Tolima (CZUT)-Anfibios. 363 records from PSUZC-Reptile Collection. 2 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 42570 records from Bird Collection of Museum and Institute of Zoology PAS. 2 records from Solving a nomenclatural conundrum: Cernosvitovia crainensis (Mršić, 1989) and Aporrectodea macvensis Šapkarev in Mršić, 1991 (Lumbricidae). 63 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 38 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 311 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 1646 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 5 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 4 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 2071 records from Collection Echinodermata SMF. 64596 records from MfN - Fossil vertebrates IV. 36 records from AIS Wildtype Populations of Arabidopsis. 8 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 1 records from A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 from Iran, and new record of N. manningi Kazmi & Kazmi, 1992 (Decapoda: Axiidea: Callianassidae). 15178 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1828 records from MEXU/Flora de Oaxaca. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 235 records from Taxonomy and natural history of the myrmecophilous genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae) from China and adjacent regions: revision of the C. jucunda species group. 1 records from On the Chilopoda from Turkey. 1 records from A new species and a new record of Horaeomorphus Schaufuss (Staphylinidae: Scydmaeninae: Glandulariini) from China. 4 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 22608 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 1 records from Mantidflies (Neuroptera, Mantispidae) from Tocantins state (Brazil): distribution and identification key. 913224 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 63 records from Chenopodium vulvaria. 2 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 3781 records from VMNH SVDM Vertebrate Paleontology. 10 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 1 records from Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China. 100 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 1 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 3 records from Two new Afrotropical genera of Scatopsidae (Diptera). 6623 records from Mammalia fossil Kleinsäuger - SMF. 4 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 76 records from Taxonomic study of the genus Hypatopa Walsingham, 1907 (Lepidoptera: Blastobasidae) in China, with descriptions of five new species. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 8 records from Taxonomic revision of Plyomydas Wilcox & Papavero, 1971 with the description of two new species and its transfer to Mydinae (Insecta: Diptera: Mydidae). 289 records from bmhs_butterfly_collection. 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 4 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 172 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 355 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 998 records from Plant of Folklore (KIDR-PL). 9 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1698 records from Collection Paleoanthropology SMF. 32 records from The soft ticks (Parasitiformes: Ixodida: Argasidae) of Mexico: species, hosts, and geographical distribution. 3455 records from MfN - Fossil plants (Paleophytic). 442 records from Mollusk Collection of Yokosuka City Museum. 18 records from EAC - Herbário Prisco Bezerra. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 490 records from Duke University. 65942 records from Museums Victoria provider for OZCAM. 2786 records from Plan de vertebrados de la Patagonia. 62 records from Herbivorie_Pflanzenebene_2008. 21 records from Trichromothrips genus-group (Thysanoptera, Thripidae) from China, with descriptions of three new species and ten new records. 150371 records from SysTax - Zoological Collections. 1 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 2 records from A new species of the stenopodidean shrimp genus Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Ryukyu Islands, Indo-West Pacific. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 16 records from Three new species of Thaloe Brescovit (Araneae: Anyphaenidae: Anyphaeninae), with descriptions of the first known females of the genus. 31 records from Sphaeriid clams. 348 records from Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 232661 records from Oklahoma Vascular Plants Database Provider. 32 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 10 records from Pteroceraphron Dessart new to the USA (Hymenoptera: Ceraphronoidea). 505678 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 11463 records from Liste des pays par taxon spécimen TOGO. 7 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 155 records from Foreign plant germplasm collections in Ghana. 1541 records from Seabirds of the Southern and South Indian Ocean. 3 records from Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae). 16 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Camiguin, Philippines Fauna. 126 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 35 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 105 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 13804 records from Collection Pisces SMF. 3 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 6 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 3 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 7813 records from MEXU/Tipos de plantas vasculares. 26 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 22 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 13 records from SPC CoFish Invertebrates Observations Niue 2005. 133 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 5 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 1 records from The current status of Neocnus Arredondo, 1961 (Mammalia: Edentata: Pilosa: Megalonichidae) and a replacement name for its junior homonym in the sea cucumber family Cucumariidae (Echinodermata: Holothuroidea: Dendrochirotida: Cucumariidae). 6 records from Zanna robusticephalica sp. nov. (Hemiptera: Fulgoromorpha: Fulgoridae) from China, with comments on some ultrastructural characters of the new species. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 3 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 200 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 17 records from Colección de Entomología - Arthropoda. 3411 records from Tasmanian Museum and Art Gallery provider for OZCAM. 25876 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 30 records from TTRS Mammals. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 6 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 9 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1001 records from Mushroom (KIDR-MR). 27 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 45 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Fósseis (ZUFMS-FOS). 269 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 21696 records from Fish specimens of Bihoro Museum. 639 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 435 records from Collection Lepidoptera SMF. 83 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 24 records from Schismatothelinae spiders (Araneae, Mygalomorphae, Theraphosidae) from Colombia: four new species and an approach to their diversity. 5189 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes. 2755 records from University of Sindh Jamshoro Herbarium. 23 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 23 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 13 records from Solomon Islands Ants 2015. 14 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 191 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 6 records from A new genus and species of a terrestrial cavernicolan planarian from Barro Colorado Island, Panama (Platyhelminthes, Tricladida, Cavernicola). 201 records from Estonian Nature Observations Database. 74661 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 8505 records from Botanical Museum, Copenhagen, Mycology Herbarium. 125 records from New species, redescriptions and phylogenetic revision of tribe Dacini (Diptera: Tephritidae: Dacinae) from India based on morphological characters. 1 records from KTU Pinophyta. 4 records from Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean. 6401 records from NCSM Mammals Collection. 14 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 4 records from A new species of Selatosomus Stephens and the occurrence of Pristilophus melancholicus (Fabricius) in China (Coleoptera: Elateridae: Dendrometrinae). 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 20027 records from Coleção de Porifera do Museu Nacional - UFRJ. 4074 records from Colección de Entomología del Instituto Alexander von Humboldt. 150 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 1 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 1 records from On the Chilopoda from Turkey. 2811 records from Insect specimens of Toyota City Nature Sanctuary. 69 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 5 records from Pelagic ctenophores from the São Sebastião Channel, southeastern Brazil. 3 records from Nouvelles fourmis de Madagascar.. 99 records from CHAS Botany Collection (Arctos). 30731 records from Vascular plants collection of Hiratsuka City Museum. 39 records from A photographic catalog of Ceraphronoidea types at the Muséum national d’Histoire naturelle, Paris (MNHN), with comments on unpublished notes from Paul Dessart. 9 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 11095 records from Colección Viva del Jardín Botánico de Bogotá. 11 records from Mammal specimens of Kawasaki Municipal Science Museum. 12 records from A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae). 41 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 6 records from A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay. 12 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 7 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 1 records from Carabodes coriaceus. 1059 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 1 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética. 322 records from The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records. 30 records from UFRN-Fungos - Herbário UFRN - Fungos. 37723 records from Colección Herbario Federico Medem Bogotá - FMB. 37 records from A checklist of marine littoral mites (Acari) associated with mangroves. 2 records from Three squat lobsters (Crustacea: Decapoda: Anomura) from tropical West Pacific seamounts, with description of a new species of Uroptychus Henderson, 1888. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 12 records from An annotated checklist of earthworms of Greece (Clitellata: Megadrili). 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 1912 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 442 records from Snow Petrel census, Reeve Hill, Windmill Islands, East Antarctica (1984-2003). 603 records from Collection of Industrial Microorganisms. 6 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 121 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 116 records from Collection Ephemeroptera - SMF. 2 records from ECOLINC: BIODIVERSITY OF THE WESTERN VOLCANIC PLAINS SIGHTINGS. 9 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 3821 records from Denver Museum of Nature & Science - Entomology. 177 records from Insecta of Costa Rica (INBio). 1 records from Four new species of the leafhopper genus Riseveinus Li (Hemiptera: Cicadellidae: Evacanthinae) from China and Thailand. 1 records from A new species of the genus Rapturella (Gastropoda: Acteonidae) from southeast Brazil. 20261 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 38 records from A review of the Barbatula loaches (Teleostei: Nemacheilidae) from north-eastern China, with the description of four new species. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 6 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 5174 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 55 records from Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species. 8 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 15 records from Revision of the Chinese species of the genus Grouvellinus Champion, 1923 (Coleoptera: Elmidae). The G. acutus species group. 7625 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 5467 records from Collection of Hymenoptera. 5 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 7 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 1 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 3 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 2 records from An integrative description of Ramazzottius subanomalus (Biserov, 1985) (Tardigrada) from Poland. 4 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 884 records from Sea shells of New South Wales. 665 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Aves (MG-ZV-A). 2 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 303 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 7 records from Redescription and designation of a neotype for Ophiothrix angulata (Say, 1825) (Echinodermata: Ophiuroidea: Ophiotrichidae). 3 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 94516 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 1 records from Herpetofauna laguna El Tinije. 3 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 194 records from Ontario Breeding Bird Atlas 1981-1985. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 2300 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 33 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 2 records from Description of two new idiocerine leafhoppers of the genus Chinaocerus (Hemiptera: Cicadellidae) from southwestern China. 1 records from Two new species of the subgenus Brachyphytodecta Bechyně, 1948 (Coleoptera, Chrysomelidae, Gonioctena) from Sichuan, Southwest China. 1072 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 18 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 4 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 43 records from Three new species of the Encarsia inaron (Hymenoptera: Aphelinidae) species group from China with a key to Chinese species. 3 records from Undocumented beetle diversity in the Southeastern United States: a case study of the minute clubbed beetles (Coleoptera: Monotomidae). 606 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 1 records from Tokunagaia Saether from China (Diptera: Chironomidae: Orthocladiinae). 4 records from Three species of Hydrobaenus Fries (Diptera: Chironomidae: Orthocladiinae) from Belarus. 4 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 95257 records from Michigan State University Herbarium Lichens. 34 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 7 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 380 records from Wichita State University Collection. 5025 records from DBG Sam Mitchel Herbarium of Fungi. 1 records from Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae). 20261 records from Collection Crustacea - ZMB. 1 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 13003 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 34 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 265 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 4 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 5 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 5 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 2 records from The polyps of Oceania armata identified by DNA barcoding (Cnidaria, Hydrozoa). 3 records from On Starengovia Snegovaya, a genus of Asian nemastomatines (Arachnida: Opiliones: Nemastomatidae). 1 records from Myriopoden von Epirus. 2 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 150 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 10 records from Dermaptera in the icipe collection. 17 records from Systematics of the New Zealand Weevil Etheophanus Broun (Curculionidae: Molytinae). 8 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 1668 records from MVZ Egg and Nest Collection (Arctos). 1418 records from Fossil (GNHM-FO). 109 records from MMFR Zingiberaceae Botanical. 6 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 9 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 2 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 48 records from Herbario HUAZ Enrique Forero. 6 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 10 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 2 records from Four new generic and 14 new specific synonymies in Pholcidae, and transfer of Pholcoides Roewer to Filistatidae (Araneae). 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 333 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 30 records from Hawk Migration Association of North America - HawkCount. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 27743 records from E. C. Smith Herbarium (ACAD). 6316 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 26 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 173 records from Colección del Museo de Ciencias Naturales “José Lorca”. 1 records from EBCC Atlas of European Breeding Birds. 2 records from Base de datos de Rana catesbeiana.. 5 records from Taxonomic revision of Saffron-billed Sparrow Arremon flavirostris Swainson, 1838 (Aves: Passerellidae) with comments on its holotype and type locality. 14 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 108 records from A taxonomic revision of Globba subsect. Nudae (Zingiberaceae). 33 records from New data on the taxonomy, distribution and host plants of Australian Epermeniidae (Lepidoptera: Epermenioidea). 11 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 184 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 157 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 111 records from The bees (Hymenoptera: Apoidea) of the Maltese Islands. 10 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 1 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 13 records from Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa. 4 records from Pyura (Tunicata: Ascidiacea: Pyuridae) on the coasts of Panama. 10 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 13934 records from Fort Hays State University Sternberg Museum of Natural History - Vertebrate. 52 records from Evaluación de la resistencia a la roya (Uromyces appendiculatus) en poblaciones silvestres y cultivadas de frijol, mediante el empleo de marcadores genéticos moleculares. 2 records from Four new species of the spider genus Cicurina Menge, 1871 from China (Araneae: Dictynidae). 320 records from pbzt_insect_biodiversity. 4 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 21 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 28 records from NZCS Upper Tapanahony Expedition 1991. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 1 records from Oppia nitens. 1 records from Tanzanian Vertebrate Collection. 6 records from Two new species of Scymnini (Coleoptera: Coccinellidae) from Karnataka, India. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 3 records from Morphology and infraciliature of two new earthworm ciliates, Hoplitophrya polymorphus sp. nov. and Anoplophrya simplex sp. nov. (Ciliophora: Oligohymenophorea: Astomatia). 603 records from Fossil (NSMK-FO). 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 1 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 283 records from HSU Vertebrate Museum Birds Collection. 21 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 4 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 32 records from Coleção de Nematoda do Museu Nacional - UFRJ. 4 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 9239 records from Carabidae of Poland. 21466 records from MEXU/Plantas Vasculares. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 1 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 242315 records from University of Michigan Museum of Zoology, Division of Insects. 51 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 2 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 2135 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 40 records from Additions to the knowledge of the land snails of Sabah (Malaysia, Borneo), including 48 new species. 119 records from Fungi specimens of Saitama Museum of Natural History. 8 records from National Museum Of Marine Science & Technology. 28600 records from Collection Ichthyologie - SNSD. 44 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey. 137 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 1129 records from Mollusca Collection of Saitama Museum of Natural History. 2 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 5 records from Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga). 1 records from Oribates fusifer. 13 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 6406 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1405 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 438 records from Fungi collection of Jyväskylä University Museum. 57 records from Nemertini - SMF. 1 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 1 records from Occurrence of some antityphod plants from Cameroon. 18373 records from Bosque Mesófilo de Montaña de México. 593029 records from NMNH Paleobiology Specimen Records. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 8631 records from DMNS Bird Collection (Arctos). 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 2 records from A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae). 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 83695 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Australian Formicidae.. 3468 records from Collection ornithologique A. Maës. 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 528 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 3 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 43 records from Mammal specimens of Komatsu City Museum. 12 records from Natural England bat roost visit records from 2013 onwards. 1 records from Ophichthus johnmccoskeri sp. nov. (Anguilliformes: Ophichthidae): a new snake eel from Indian waters, Bay of Bengal. 2 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 15 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 8564 records from Bird specimens of Himeji City Science Museum. 137319 records from Naturalis Biodiversity Center (NL) - Aves. 3659 records from National Stag Beetle Surveys (Great Stag Hunts). 13 records from Seven new species of the genus Xestoleberis (Ostracoda: Podocopida: Cytheroidea) from the Fiji Archipelago. 35 records from RISC Non-Native Species Records for Muntjac. 363 records from The cicadas (Hemiptera: Cicadidae) of India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka: an annotated provisional catalogue, regional checklist and bibliography. 9995 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 10 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1565 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 40 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 392 records from Publicación de la obra: American species of Acacia (Leguminosae; Mimosoideae). 1 records from A new species of Dinotoperla Tillyard, 1921 from the Shoalhaven Catchment, New South Wales, Australia (Plecoptera: Gripopterygidae). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 22 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 1 records from BioFokus. 11 records from Glossing over cryptic species: Descriptions of four new species of Glossodoris and three new species of Doriprismatica (Nudibranchia: Chromodorididae). 5 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 227 records from An annotated checklist of the Chilopoda and Diplopoda (Myriapoda) of the Abrau Peninsula, northwestern Caucasus, Russia. 2 records from Códigos de barras de helmintos de anfibios y reptiles de México. 30239 records from TTU Mammals Collection. 69917 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 11 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 973 records from CNAN/Scorpiones. 102 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 3 records from Aplectana nordestina n. sp. (Nematoda: Cosmocercidae) parasitizing Leposternon polystegum (Squamata: Amphisbaenidae) from Northeastern, Brazil. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 357 records from bmhswatsonshellcollection. 5 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 2775 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 1 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 33193 records from Diversity of microbial community (bacteria, micro-eukaryotes and fungi) in the Passage of Lascaux Cave.. 7 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 33 records from Taxonomic revision of the Neotropical genus Caenopangonia Kröber, 1930 (Diptera: Tabanidae). 7 records from A new species of Orthosiphon (Lamiaceae) from Angola. 2 records from Persianorchestia, a new talitrid genus (Crustacea: Amphipoda: Talitridae) from Gulf of Oman, Iran. 279 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2443 records from Cnidaria MZS. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 22 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 5 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 6539 records from Spider (NSMK-SP). 26 records from Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus. 34 records from OUPR - Herbário "Professor José Badini". 2323 records from Colección de Asterales del Museo Botánico CORD. 37 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 1 records from On several species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa), including the description of a new species. 47 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 458 records from Westmead Mycology Culture Collection. 20854 records from DSMZ Prokarya Collection Catalogue. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 1924 records from NZCS Invertebrates Old Collection Before 1987. 97 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 2 records from Hiding in plain sight on Gunung Muria: A new species and first record of rock gecko (Cnemaspis Strauch, 1887; Squamata, Gekkonidae) from Java, Indonesia. 100 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 14339 records from Bird collection of National Museum of Nature and Science. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 5 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 30 records from bmhs_echinoderm_collection. 271 records from Herbier National du Gabon. 6 records from Mammalia (JNHM-MM). 10 records from Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia. 9 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 13947 records from The Vascular Plants Collection of the University of Goettingen. 7 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 2 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 9 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 400 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 41 records from Congruence between morphology and molecular data supports the distinction between the snapping shrimps Alpheus macrocheles and A. amblyonyx (Caridea, Alpheidae). 4 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 9754 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 4625 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1772 records from Andes to Amazon Biodiversity Program. 26829 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 73 records from Collection Echinodermata - ZMB. 11 records from Four new species of Brueelia Kéler, 1936 (Phthiraptera: Ischnocera) from African hosts, with a redescription of Nirmus bicurvatus Piaget, 1880. 27 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 7 records from Two new species of armoured spiders from Vietnam and Cambodia (Araneae: Tetrablemmidae: Pacullinae). 8 records from Inventario herpetofaunístico del noroeste de Hidalgo. 2998 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 5 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 44 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 9798 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 7 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 111 records from Jardín Botánico Atlántico, Gijón: JBAG. 7320 records from Aves Collection of Institute of Systematics and Evolution of Animals. 2843 records from Universidad Autónoma de Madrid, Biología, Acalypha. 6230 records from Herbarium specimens of CBNA (GAP). 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 15505 records from CONN. 42060 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 7 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 12288 records from ISM Mammalogy Collection. 40965 records from The avian collection at the Natural History Museum, Oslo, Norway. 374 records from Medicinal potential of African plants (Togo). 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 1719 records from Nijmegen Natural History Museum (NL) - Herbarium. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 37 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 2 records from Studies in Guatemalan Ensifera: Mayacephalus (Orthoptera: Tettigoniidae) a new cone-headed katydid genus. 282 records from MfN - Fossil invertebrates IIa. 9 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 5 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 11462 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 32367 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 3 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 2 records from Notes on a small collection of phaneropterine bush-crickets (Insecta: Orthoptera: Tettigonioidea) from Central and Southern Madagascar with the description of two new species. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 1 records from Zetes lucorum. 951 records from Collection Arachnida - ZSRO. 1415 records from Collection botanique Le Grand A. (BOUM). 24471 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 9 records from Cyanobacteria of Algal Collection of Soil Science Institute (ACSSI). 11 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 11 records from Revision of the Protohermes species from Tibet, China (Megaloptera: Corydalidae). 6 records from Review of the genus Cyrtosia Perris (Diptera: Mythicomyiidae: Platypyginae) in Iran, with description of three new species. 2 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 1 records from CNAN/Arañas sinantrópicas. 156 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 173415 records from Hymenoptera specimen database of Kyushu University. 49578 records from Finnish Floristic Database (Literature Sources). 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 27 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 30 records from museums-hepertology-biodiversity-records. 2 records from A new species of anole from Parque Nacional Volcán Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops). 8848 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017). 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 1309 records from Mongolian Plant (MMNH-PL). 1350 records from Echinoderm specimens of Ryukyu University Museum (Fujukan). 46 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 1 records from A new species of genus Eulimnadia Packard, 1874 (Branchiopoda: Spinicaudata: Limnadiidae) from India with an updated key for some Indian species. 26371 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 15 records from Description of the new genus Nebulene Volynkin & Černý, gen. nov., with a new species from Thailand and Vietnam (Lepidoptera, Erebidae, Arctiinae). 64 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 2 records from Description of a new species of Miltochrista Hübner from Vietnam, with eight new combinations (Lepidoptera, Erebidae, Arctiinae). 11 records from Atlas of Life in the Coastal Wilderness - Sightings. 49 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 25 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 1536 records from Records of the Queensland Plant Pathology Herbarium. 2 records from A review of the Arcuphantes species with the genitalia of arcuatulus - type (Araneae, Linyphiidae). 223 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 10102 records from Régénération naturelle de ligneux du Sénégal. 2 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 7 records from Definition of the Bradysia luctifica group (Diptera, Sciaridae), with the description of five new species. 10 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 995 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 4847 records from Polish seed gene bank – historical passport data of accessions. 3 records from A new species of Misetus Wesmael, 1845 (Hymenoptera, Ichneumonidae, Ichneumoninae, Phaeogenini) from Italy, with updated key to the females of Palaearctic species. 2420 records from Plant (NHMC-PL). 1594 records from Musée Vert ornithology collection. 16 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 419 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 9930 records from Colección Herpetológica "Lic. Blanca Beatriz Alvarez" - Facultad de Ciencias Exactas y Naturales y Agrimensura - Universidad Nacional del Nordeste. 5 records from Herbier Husnot, Hepatica Galliae. 812 records from Espèces végétales inventoriées dans les formations et strates de la forêt classée de Missahoe au Togo en 2017.. 2 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 10 records from A curious new genus of Keroplatini (Diptera: Keroplatidae) from Guatemala. 17 records from Descriptions, transference and new records of Lamiinae from Central and South America (Coleoptera, Cerambycidae). 1 records from Contribution to the knowledge of the cavernicolous beetle genus Aspidaphaenops Uéno from Guizhou (Coleoptera: Carabidae: Trechinae). 6 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part IV. Genera Eugnoriste Coquillett and Keilbachia Mohrig. 7024 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 89 records from A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea. 10449 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 146 records from A new species of Astropecten (Echinodermata: Asteroidea: Paxillosida: Astropectinidae) and a comparison of the Astropecten species from the Gulf of Mexico and the East Florida Shelf. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 360870 records from Eremaea. 60 records from Marine Offshore Seabed Survey data held by JNCC. 21 records from Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology. 29 records from A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini). 15 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 777 records from University of Manitoba (WIN) - Lichen Collection. 9 records from Larvae of three East-Asian species of Nemoura (Plecoptera: Nemouridae). 3598 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 24340 records from Natural History Museum Rotterdam (NL) - Chordata collection. 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 6 records from Revision of the leafhopper genus Gurawa (Cicadellidae: Deltocephalinae: Chiasmini) from Pakistan with description of a new species. 309936 records from Herbarium of Taiwan Forestry Research Institute. 60 records from NIWA Invertebrate Type Collection. 2 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 47 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 16 records from Malawi-Histeridae-Biodiversity-Data. 1 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 15942 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 8 records from Contribution to the knowledge on the spider wasps genus Morochares Banks, 1934 (Hymenoptera: Pompilidae) from China. 10 records from A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 4 records from Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 13 records from The first record of Cuculliaumbratica (Lepidoptera: Noctuidae) from Japan. 12792 records from Naturalis Biodiversity Center (NL) - Echinodermata. 6 records from A new species of the Amolops monticola group (Anura: Ranidae) from southwestern Yunnan, China. 1 records from Oribates calcaratus. 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 9 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 461340 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 744 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 292 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 129 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 1272 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 44 records from Estudio ecológico y genético de las poblaciones de Rhizophora mangle en México. 2 records from Porifera ZMK. 1 records from Nothrus furcatus. 3 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 127 records from New species and distribution records for Mexican and Central American Cerambycidae (Coleoptera). 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 12 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 707 records from The Muscidae (Diptera) of Armenia. 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 11114 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 54 records from New records of the family Chalcididae (Hymenoptera: Chalcidoidea) from Egypt. 1 records from Oribates flammula. 16 records from Ceratophila, a new genus of erotylid beetles (Erotylidae: Pharaxonothinae) inhabiting male cones of the cycad Ceratozamia (Cycadales: Zamiaceae). 11498 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 21362 records from University of Tennessee Bryophyte Herbarium. 23 records from Revision of the Agrilus humilis species-group (Coleoptera: Buprestidae: Agrilini) with description of thirteen new species from Southeastern Asia. 3305 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 9726 records from Paleobotany Specimens. 15936 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 685 records from CNIN/Lepidoptera. 64 records from Herbarium of Lars Levi Laestadius. 79 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 1 records from Antarctic Euphausiacea occurence data from Polish FIBEX expeditions. 4 records from Amphibiens de Guyane. 19 records from Three new species of Onychiuridae Lubbock, 1871 (Collembola, Poduromorpha) from Iran. 3 records from Review of the leafhopper genus Kalasha Distant (Hemiptera: Cicadellidae: Hylicinae). 2 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 106100 records from Fish (NSMK-PI). 1 records from Sclerotinia cirsii-spinosissimi, a new species from the Alps. 10779 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 2 records from High diversity of Caligus species (Copepoda: Siphonostomatoida: Caligidae) in Taiwanese waters. 6 records from Collection Myriapoda - SNSD. 4693 records from Fiocruz/CCER - Coleção de Ceratopogonidae. 1 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 1100 records from Bryophyte Herbarium, Oslo (O-B). 9 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 1268 records from The Shigeru Eda Insect Collection of The University Museum, The University of Tokyo. 203 records from Review of the African genera Arantia Stål and Goetia Karsch (Orthoptera: Tettigoniidae: Phaneropterinae). 1 records from Celaeno detrita. 950 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 362 records from FBIP: Systematics of South African Hymenoptera. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 4 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 8 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 2 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 5 records from New species and synonymy in the genus Corotoca Schiødte, 1853 (Coleoptera, Aleocharinae, Corotocini). 5 records from Integrative taxonomy of Hemimycale (Hymedesmiidae: Poecilosclerida: Demospongiae) from Southeastern Brazil, with the description of two new species. 5 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 9399 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 11 records from On The Relationships of the Spider Genus Cybaeodes (Araneae, Dionycha). 39 records from Navigator, a new endemic genus of Cetoniinae (Coleoptera: Scarabaeidae) from Australia, with descriptions of two new species and behavioural studies. 27 records from A new endemic species of Willowsia from Florida (USA) and descriptive notes on all New World Willowsia (Collembola: Entomobryidae). 2 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 1 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 1 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 702 records from Factual Database of Native Flora Seeds in Korea. 1050 records from DBL_Life. 422 records from The types of Phasmida in the Natural History Museum, London, UK. 6 records from Taxonomy of Oceanapia Norman, 1869 (Demospongiae: Haplosclerida: Phloeodictyidae) from the Brazilian coast. 23 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 3 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 2608 records from Auckland Museum NZ Marine Collection. 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 239 records from Acari Collection - Instituto Nacional de Pesquisas da Amazônia. 2002 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 2 records from A new skate genus Orbiraja (Rajiformes: Rajidae) from the Indo-West Pacific. 1 records from Description of Tottonophyes enigmatica gen. nov., sp. nov. (Hydrozoa, Siphonophora, Calycophorae), with a reappraisal of the function and homology of nectophoral canals. 90 records from Thrips (Thysanoptera) in Norway. 2 records from A new species of Homo from the Late Pleistocene of the Philippines. 2 records from One new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Chongqing, China. 1 records from Two new species of cave-dwelling Charinus Simon, 1892 from Brazil (Arachnida: Amblypygi: Charinidae). 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 21 records from Invertebrate collection. 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 20 records from Report of Caridina babaulti Bouvier, 1918 (Crustacea: Decapoda: Caridea: Atyidae) and description of a new species Caridina kutchi sp. nov. from Gujarat, India. 8 records from Feather mites of the subfamily Proctophyllodinae (Acari: Proctophyllodidae) from passerines (Aves: Passeriformes) in Costa Rica. 1 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 2925 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 67 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 25032 records from UWFC Ichthyology Collection. 23 records from On the wasp-mimicking sharpshooter genus Propetes Walker, 1851 (Hemiptera: Cicadellidae: Cicadellinae): description of a new species, proposal of a new synonymy, and distributional notes. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 27 records from The genus Arocatus in Taiwan (Hemiptera: Heteroptera: Lygaeidae). 8 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 81 records from In the footsteps of history: the bees of the genus Hylaeus Fabricius (Hymenoptera, Apoidea: Colletidae) collected by V. I. Roborovsky and P. K. Kozlov in Northwest China (1895 - 1926). 1 records from A new species, new synonymy and new records of Mexican and Central American Xyleborini (Coleoptera: Curculionidae: Scolytinae). 39 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Phoenicopteridae. 4720 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 2 records from Macrohongos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 45 records from Excavating sponges from the Pacific of Central America, descriptions and a faunistic record. 3431 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 10804 records from CUMV Fish Collection. 1 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 886967 records from EURISCO, The European Genetic Resources Search Catalogue. 1880 records from Données ONF Faune-Flore-Fonge. 2116 records from Collection entomologique Pierre Lachiver. 2661432 records from The New York Botanical Garden Herbarium (NY). 119 records from Richard Staniforth Herbarium (UWPG). 48979 records from Naturalis Biodiversity Center (NL) - Paleobotany. 44 records from List of Facultative and Corallivore Species recorded in Vava'u. 24131 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 69756 records from Collection Arachnology SMF. 3 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 1232 records from University of Tennessee Fungal Herbarium. 90413 records from University of Michigan Museum of Zoology, Division of Mollusks. 580 records from Banco de información sobre características tecnológicas de maderas mexicanas. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 135 records from Data from CRSN herbarium digitization initiative under BID-funded project. 3 records from Mammalia (SMNH-MM). 5 records from Eight new species of the genus Clubiona Latreille, 1804 from Xishuangbanna Rainforest, southwestern China (Araneae, Clubionidae). 6249 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 2854 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 27925 records from iNaturalist Research-grade Observations. 17 records from First record of the genera Centistoides van Achterberg and Pygostolus Haliday (Hymenoptera: Braconidae) in Brazil, with the description of new species. 8406 records from Conservatoire Botanique Pierre Fabre. 4 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 3204 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 52 records from New taxa of the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China, with comments on the importance to taxonomy of the left tegmen. 5 records from A new leaf-mining moth, Caloptilia aesculi, sp. nov. (Lepidoptera: Gracillariidae: Gracillariinae) feeding on Aesculus chinensis Bunge (Hippocastanaceae) from China. 7 records from To the revision of the genus Thionia Stål (Hemiptera, Fulgoroidea, Issidae), with description of new genera and new subtribe. 76317 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 4 records from DASSH Data Archive Centre Academic Surveys. 147 records from Measurements of elephant tusk trophies taken in Botswana 2004. 6 records from A new species of Deltaspis Audinet-Serville (Coleoptera: Cerambycidae: Cerambycinae) from Mexico. 2 records from A new species of the endemic Australian genus Hyptiogaster Kieffer (Hymenoptera: Gasteruptiidae). 1118 records from Herbario MAIA, colección Manuel Martín Bolaños. 3404 records from Akita Prefectural Museum, Insect Collection. 14478 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association ( SAW-2011-ZFMK-3). 8 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 1 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 8 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 513 records from Quoll sightings register for Nth QLD. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 39 records from The goblin spider genus Ischnothyreus (Araneae, Oonopidae) in Java and Sumatra. 25125 records from University of Florida Invertebrate Paleontology. 1 records from A new species of the genus Comidoblemmus Storozhenko & Paik (Orthoptera: Gryllidae) from Xizang, China. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 2 records from Five new species of Caddisflies (Trichoptera: Insecta) from Upper Tenasserim Range, Thailand and Myanmar. 3 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 13 records from Lerneca inalata beripocone subsp. nov. (Orthoptera: Phalangopsidae; Luzarinae): a new taxon for the northern Pantanal of Brazil. 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 21261 records from Sukkulentensammlung Zürich. 3 records from Note su alcune specie di chilopodi della regione palestinese. 122 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 2 records from Capture Mark Recapture Data for Scottish Elasmobranchs: 2009-2018. 160 records from New South Wales Bird Atlassers. 5341 records from Bacteria Collection in BCRC. 98 records from Seawater carbonate chemistry and biological processes of coccolithophore (Gephyrocapsa oceanica and Coccolithus pelagicus ssp. braarudii) during experiments, 2011. 2 records from The discovery of the spider genus Putaoa (Araneae, Pimoidae) in Taiwan with the description of a new species, including its web architecture. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 2 records from A new species of Teleogryllus (Teleogryllus) Chopard, 1961 from Yunnan, China (Orthoptera: Gryllidae: Gryllinae). 46372 records from Herbarium of Namur. 12102 records from UAM Bird Collection (Arctos). 6 records from A new species, genus and tribe of Sapotaceae, endemic to Madagascar. 9 records from Taxonomic review of the rare Mexican snake genus Chersodromus (Serpentes: Dipsadidae), with the description of two new species. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 6 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 2 records from Revision of the Mesoamerican species of Calolydella Townsend (Diptera: Tachinidae) and description of twenty-three new species reared from caterpillars in Area de Conservación Guanacaste, northwestern Costa Rica. 477 records from UTEP Herpetology Osteology (Arctos). 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 6 records from A new species of the genus Phytoecia Dejean, 1835 (Coleoptera: Cerambycidae) from Greece. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 11 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 37 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 20 records from Tsetse flies of East Africa update. 83 records from European bison in Białowieża Primary Forest. 1 records from Pelops phaeonotus. 2 records from Amphibia ZMK. 1 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 6 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 1 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20322 records from pins. 29 records from Collection Crustacea - KAUMM. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 1 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 1 records from Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea. 273 records from Preservation of ancient eukaryotic DNA in methane hydrate-associated marine sediments.. 85 records from Prairie Fen Biodiversity Project. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 1 records from Descriptions of new and little-known land snail taxa from Turkey, and establishment of a new genus (Gastropoda, Pulmonata: Lauriidae, Enidae and Vitrinidae). 1333 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 2 records from The probable larva of Anotogaster gregoryi Fraser, 1923, with new distributional records of the genus from northern Thailand (Odonata: Cordulegastridae). 3264 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 189 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1 records from Colección Mastozoológica de la Universidad Distrital Francisco José de Caldas. 3 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 49 records from Mammal specimens of Natural History Museum, Kishiwada City. 5 records from On three species of the trapdoor spider Genus Cyclocosmia from China (Araneae, Halonoproctidae). 8 records from Description of four new species of Ochlerini from South America (Hemiptera: Pentatomidae: Discocephalinae). 7 records from A new subspecies of Delias agostina Hewitson (Lepidoptera: Pieridae: Pierinae) from Hainan Island. 2 records from Poecilia (Pamphorichthys) akroa, a new poeciliid species (Cyprinodontiformes: Poeciliidae) from the Rio Tocantins basin, Brazil. 4 records from A new Agraecina spider species from the Balkan Peninsula (FYR Macedonia) (Araneae: Liocranidae). 1 records from The millipede Typhloglomeris caucasica Golovatch, 1975 found epigeically (Diplopoda, Glomerida, Glomeridellidae). 3528 records from Herbario de la Universidad de La Laguna:TFC-Bry. 24 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 3877 records from Colección de Zoología Invertebrados - Helmintología. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 7086 records from EFC - Herbário Escola de Florestas Curitiba. 24 records from The genus Dichopygina gen. n. (Diptera: Sciaridae). 7170 records from The Bergius Herbarium. 2 records from On the subgenus Eurysunius Reitter of Turkey VI. Two new species from Sivas province in central northern Anatolia, with a key to Turkish species (Coleoptera: Staphylinidae: Paederinae, Astenus). 1938 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 4013 records from Museo Nacional de Ciencias Naturales, Entomología. 2 records from Range extension of the rare braconine genus, Lyricibracon Quicke (Hymenoptera: Braconidae), with the description of a new species from India. 44 records from A review of the families and genera of the superfamily PLATYSCELOIDEA Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. 4 records from A new species of Phaenostoma d’Orchymont, 1937 (Coleoptera: Hydrophilidae) from Brazil. 51 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 2 records from Systematic position of two Pliocene carditids with description of Akardita n. gen. and A. iberica n. sp. (Bivalvia: Carditidae). 2 records from Corvids Literature Database. 5 records from Ophion scutellaris species group specimen data. 18621 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7003 records from Liste des récoltes par Herbier de dépôt TOGO. 21 records from The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini). 2 records from Código de barras de ocho complejos de especies de aves mexicanas. 24000 records from Insects Specimens of Kagoshima Prefectural Museum. 1 records from Systematics of Guajirolus ektrapeloglossa Flowers 1985 (Ephemeroptera: Baetidae). 1 records from Status and spatial diversity of Sorghum wild species in Malawi.. 147 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 4 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime. 3 records from Contribution to the knowledge of the genus Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae), with the description of two new species from Indonesia. 106 records from Cretaceous nannofossils in profile Serre Chaitieu, SE France. 3 records from Two new species and new records of the genus Parachironomus Lenz, 1921 (Diptera, Chironomidae) from northern Russia. 73043 records from BugGuide - Identification, Images, & Information For Insects, Spiders & Their Kin For the United States & Canada. 5 records from University of Calgary Herbarium - Lycophytes and Monilophytes. 18073 records from UCBG TAPIR Provider. 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 46 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 11 records from A Cryptic Invasion in the Western Atlantic: Presence of the Fouling Barnacle Megabalanus zebra (Darwin, 1854) (Crustacea, Cirripedia) in the Caribbean Sea. 103 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 13330 records from Montana State University - Billings. 2 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 3 records from Palaeopsylla (Palaeopsylla) aysenurae n. sp., a new ctenophthalmid flea (Siphonaptera: Ctenophthalmidae) from Turkey. 2 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 36 records from The genus Acellomyia González, a new taxonomic arrangement of its species and descriptions of a new genus and two new species from southern South America (Diptera: Tabanidae: Diachlorini). 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 1 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 3 records from Pseudoamycle polylepisae gen. et sp. nov., a fulgorid from the highlands of Northern Chile (Hemiptera: Fulgoridae). 69 records from Studies on neotropical Phasmatodea XVII: Revision of Phantasca Redtenbacher, 1906, with the descriptions of six new species (Phasmatodea: Diapheromeridae: Diapheromerinae). 841 records from Flora of Westgate Park - Photos from Lyn Allison. 7 records from The taxonomic and phylogenetic status of some poorly known Anolis species from the Andes of Colombia with the description of a nomen nudum taxon. 3 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 977 records from Habitat and host related variation in sponge bacterial communities in Indonesian coral reefs and marine lakes. 2 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 67 records from Weevils of Poland. 11 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 3 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 1 records from Arachnida of Costa Rica (INBio). 53 records from Neotype designation for Sphingius thecatus Thorell, 1890, synonymies, new records and descriptions of six new species from Southeast Asia (Araneae, Liocranidae). 16 records from Occurrence of some antimalarial plants from Cameroon. 24 records from Seawater carbonate chemistry, nutrients, and Calcidiscus leptoporus (strain RCC1135) growth rate and calcification rate during experiments, 2012. 9 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 94 records from Collection Reptilia fossil SMF. 9 records from The Pinnotheridae of the northeastern Pacific (Alaska to Mexico): zoogeographical remarks and new bivalve hosts (Crustacea, Brachyura, Pinnotheridae). 9 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 1 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 12 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 1 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 1 records from Alloionema californicum n. sp. (Nematoda: Alloionematidae): a new alloionematid from USA. 3 records from Bledius hyalinus sp. nov. (Coleoptera: Staphylinidae: Oxytelinae), of the forcipatus group, first recorded from coastal Brazil. 54 records from The Jordan theropod (Maastrichtian, Montana, U. S. A.) referred to the genus Aublysodon.. 3 records from Barsine deliciosa, a new species from China (Lepidoptera, Erebidae, Arctiinae). 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 1638 records from Herbario Amazónico Colombiano. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 2 records from Discovery of the subfamily Rhopalomutillinae (Hymenoptera: Mutillidae) in China and description of Pherotilla brothersi sp. nov.. 3 records from Galathea II, Danish Deep Sea Expedition 1950-52. 2 records from Antarctic Parborlasia corrugatus. 657 records from NCSM Non-molluscan Invertebrates Collection. 3162 records from The AAU Herbarium Database. 732 records from DSMZ Collection of Plant Viruses. 1 records from Murcia ephippiata. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 7 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 587 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 37 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 251 records from Database about reference specimens for medicinal plants, in the Apocynaceae family, owned by CNARP. 487 records from Colecção Entomológica do Museu de História Natural de Maputo. 210017 records from Invert Paleo Specimens. 44 records from Hypogean macro-Crustacea records. 296 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rallidae. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 6 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 3 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 2 records from Bryochoerus liupanensis sp. nov. and Pseudechiniscus chengi. sp. nov. (Tardigrada: Heterotardigrada: Echiniscidae) from China. 17 records from New data on the genus Domene (Coleoptera: Staphylinidae: Paederinae) of mainland China. 44347 records from Robert F. Hoover Herbarium, Cal Poly State University. 1170 records from Collection Polychaeta - ZSRO. 23 records from Chinese species of the genus of Agnesiella Dworakowska (Hemiptera: Cicadellidae: Typhlocybini), with four new species and four new records. 11 records from Specimens of Huffmanela lusitana of the Collection of Pathology of IPMA. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 40 records from Revision of the genus Metaterpna Yazaki, 1992 (Lepidoptera, Geometridae, Geometrinae), with description of a new species from China. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 15 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 2 records from Mimogonellus dreybrodti sp. n., a new cave-inhabiting Osoriinae from Laos (Coleoptera: Staphylinidae). 9 records from Cleaning old cabinets: revealing the taxonomy of Sri Lankan wolf spiders (Araneae, Udubidae and Zoropsidae). 1851 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 9118 records from MSB Bird Collection (Arctos). 237 records from Naturhistorisches Museum Mainz, Zoological Collection. 5 records from Coleophora meridiogallica Baldizzone, Huemer & Nel, sp. n. from France (Lepidoptera, Coleophoridae). 38 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 14 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 9944 records from Ichthyology Collection - Royal Ontario Museum. 22575 records from Living plant collection of Meise Botanic Garden. 23 records from Revision of African Apiocera (Diptera: Apioceridae). 3 records from Tejidos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 34 records from Gunma Museum of Natural History, Fungi Specimen. 13977 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 5498 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 52337 records from Other BSBI Scottish data up to 2012. 5118 records from Endemic plants of the Congo basin. 23 records from Two new genera and five new spec
Keywords: GBIF; biodiversity; species occurrences